2021
DOI: 10.3389/fpubh.2021.794307
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Self-Reported Screen Time, Social Media Addiction, and Sleep Among Norwegian University Students

Abstract: The aim of this study was to assess the relationship between daily screen time and sleep, evening screen time and sleep, and between social media addiction and sleep in a student population. This cross-sectional study is based on data from a national survey of all college and university students in Norway (the SHoT2018 study; n = 49,051). The sleep outcomes were sleep duration, sleep onset latency, sleep efficiency, and insomnia operationalized according to formal DSM-5 criteria. The results show a strong nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 53 publications
1
20
1
4
Order By: Relevance
“…As far as we know, the library of this university is closed at 10:30 PM, the study room is turned off at 11:00 PM at night, and the dormitory is set up with access control at 11:00 PM. Furthermore, our study found that average daily screen time of medical students was ~4 h, which was lower than the level of previous studies (7 h) ( 46 ). This may be another reason that medical students have a lower rate of short sleep than other university students.…”
Section: Discussioncontrasting
confidence: 91%
“…As far as we know, the library of this university is closed at 10:30 PM, the study room is turned off at 11:00 PM at night, and the dormitory is set up with access control at 11:00 PM. Furthermore, our study found that average daily screen time of medical students was ~4 h, which was lower than the level of previous studies (7 h) ( 46 ). This may be another reason that medical students have a lower rate of short sleep than other university students.…”
Section: Discussioncontrasting
confidence: 91%
“…From the second stage to now, the objects of studies have become more refined, including smartphone addiction, anxiety, sedentary behavior, or daily diet ( 64 , 79 ). One reason is that researchers have learned more about sleep gradually, and another may be that students' lives changed dramatically during the epidemic, which affected their physical and mental health and health-related behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Estos datos son coherentes con estudios previos en población universitaria (Cellini et al, 2021;de la Portilla Maya et al, 2019;Durán et al, 2017;Fawzy & Hamed, 2017), y consistentes con la evidencias en distintos grupos etarios, en los cuales se reporta una menor calidad del sueño asociada al género femenino, posiblemente debido a diferencias en la arquitectura del sueño en la fase "no-REM" (Mallampalli & Carter, 2014) y a las respuestas fisiológicas generadas a partir del ciclo menstrual (Colten et al, 2006). Una de las posibles causas de la mala calidad del sueño es un mayor tiempo de exposición a pantallas (Hjetland et al, 2021;Muhammad & Hussain, 2021) y su uso cercano a la hora de acostarse (Guo et al, 2021;Islam et al, 2021). Un mayor tiempo en el uso de dispositivos electrónicos se asocia a un empeoramiento en la calidad del sueño, una latencia del sueño elevada, y hora de levantarse más tarde (Amra et al, 2017;Christensen et al, 2016;El Hangouche et al, 2018).…”
Section: Discussionunclassified